Forty years of the description of brown spider venom phospholipases-D - Gremski, Luiza Helena; Da Justa, Hanna Câmara; Da Silva, Thaís Pereira; Polli, Nayanne Louise Costacurta; Antunes, Bruno César; Minozzo, João Carlos; Wille, Ana Carolina Martins; Senff-Ribeiro, Andrea; Arni, Raghuvir Krishnaswamy [UNESP]; Veiga, Silvio Sanches (MDPI, 2020)
Spiders of the genus Loxosceles, popularly known as Brown spiders, are considered a serious public health issue, especially in regions of hot or temperate climates, such as parts of North and South America. Although the venoms of these arachnids are complex in molecular composition, often containing proteins with distinct biochemical characteristics, the literature has primarily described a family of toxins, the Phospholipases-D (PLDs), which are highly conserved in all Loxosceles species. PLDs trigger most of the major clinical symptoms of loxoscelism i.e., dermonecrosis, thrombocytopenia, hemolysis, and acute renal failure. The key role played by PLDs in the symptomatology of loxoscelism was first described 40 years ago, when researches purified a hemolytic toxin that cleaved sphingomyelin and generated choline, and was referred to as a Sphingomyelinase-D, which was subsequently changed to Phospholipase-Dwhen itwas demonstrated that the enzyme also cleaved other cellular phospholipids. In this review, we present the information gleaned over the last 40 years about PLDs from Loxosceles venoms especially with regard to the production and characterization of recombinant isoforms. The history of obtaining these toxins is discussed, as well as their molecular organization and mechanisms of interaction with their substrates. We will address cellular biology aspects of these toxins and how they can be used in the development of drugs to address inflammatory processes and loxoscelism. Present and future aspects of loxoscelism diagnosis will be discussed, as well as their biotechnological applications and actions expected for the future in this field.
Keywords: Biochemical and biological activities; Brown spider; Phospholipases-D; Venom